Vector-valued almost automorphic distributions and vector-valued almost automorphic ultradistributions - M. Kostic, D. Velinov (Department of Mathematics and Informatics, Faculty of Sciences, University of Novi Sad, Serbia, 2018)
In this paper, we introduce the notations of a vector-valued almost automorphic distribution and a vector-valued almost automorphic ultradistribution, working in the framework of complex Banach spaces. We prove several structural characterizations for the introduced classes.
Keywords: vector-valued almost automorphic distributions, vector-valued almost automorphic ultradistributions, Banach spaces